Deposition and Characterization of Platinum and Palladium Nanoparticles on Highly Oriented Pyrolytic Graphite - Elizondo, Nora; Galvan, Donald H.; Alvarez-Contreras, Lorena; Tel-Vered, Ran; Cruz-Lopez, Arquímedes; Obregon, Ricardo; Belmares-Perales, Sergio; Garcia-Mendez, Manuel; Vazquez-Cuchillo, Odilon; Zaldivar, Antonio A. (IntechOpen, 2012)
None